Oral Manifestations of HIV Infections - A Review - Akhter, Mst Fatema; Quayum, Shaheen Lipika; Ali, Afrin Binta; Mamoon, Zia; Umar, Badar Uddin; Ali, Sams Sazzad (Bangladesh Journal of Physiology and Pharmacology, 2010)
Oral disease is frequently associated with HIV. Factors that predispose to HIV-related oral conditions include CD4+ cell count of less than 200/μL, plasma HIV RNA levels greater than 3000 copies/mL, xerostomia, poor oral hygiene, and smoking. While nearly all oral disorders associated with HIV infection also occur in other conditions characterized by immunosuppression, no other condition is associated with as wide and significant a spectrum of oral disease as is HIV infection. Many HIVassociated oral disorders occur early in HIV infection, not infrequently as the presenting sign or symptom. Thus, early detection of associated oral disease should, in many cases, result in earlier diagnosis of HIV infection. HIV-related oral abnormalities are present in 30% to 80% of HIV-infected individuals, and these abnormalities are often inaccurately described in medical care. Rates of treatment for oral conditions are also very low; findings in 1424 adults in the AIDS Cost and Utilization Study indicated that only 9.1% received treatment for oral manifestations of HIV diseases. Factors predictive of receiving oral care included education beyond a high school level, participation in clinical trials, and utilization of support services such as medical social workers. Likewise, awareness of the variety of oral disorders which can develop throughout the course of HIV infection, and coordination of health care services between physician and dentist, should improve overall health and comfort of the patient. This paper reviews the clinical aspects of HIV-associated oral disorders. Key Words: HIV, oral manifestations, oral diseases DOI: 10.3329/bjpp.v23i1.5728 Bangladesh J Physiol Pharmacol 2007; 23(1&2) : 25-30